How does the consumption of processed food affect the pathogenesis of various diseases? - literature review - Smuszkiewicz-Różański, Paweł; Różańska-Smuszkiewicz, Gabriela; Koszyczarek, Karolina; Kotowska, Maja; Zamirska, Wiktoria; Ziemiański, Albin; Zięba, Katarzyna; Zygmunt, Anna (Journal of Education, Health and Sport, 2024)
Introduction and purpose: With the development of civilization, the amount of technology enabling food processing increases. Due to the implementation of these procedures, food can gain new properties that will make it more attractive in the eyes of the consumer. The aim of our work is to collect information on the relationship between the consumption of processed and ultra-processed food and the development of various diseases, with particular emphasis on civilization diseases. State of knowledge: Processed food often contains non-nutritive ingredients, for example, artificial food additives, which have a negative impact on health. Numerous studies demonstrate the correlation between the consumption of ultra-processed food and the development of various diseases. Scientific research suggests that ultra-processed foods may lead to addictive behavioral and biological responses through their reinforcing effects. It also influences the development of various conditions, including obesity, type II diabetes, cardiovascular diseases, depression, and anxiety. Furthermore, its components pass through the placenta. Summary: In light of the research discussed, we are convinced that we cannot remain indifferent to the role of ultra-processed food in the pathogenesis of many diseases. Its multidirectional negative effects show that it is worth conducting further research to discover more consequences of its mechanisms. At the same time, consumers should become more aware of food composition data to be able to make conscious choices and countries should strive to change the food policies.